STRATEGI KOMUNIKASI GERAKAN PEMUDA ANSOR DALAM MENINGKATKAN PARTISIPASI BERORGANISASI - Athoilah Aly Najamudin; Muhammad Sahlan; Mochamad Ikfi Hidayatullah (Department of Islamic Community Development, Faculty of Dakwah,Universitas Islam Ibrahimy Banyuwangi, 2024)
This article discusses the communication strategy of the Ansor Youth Movement (GP) in Kabat district to enhance the participation of Nahdlatul Ulama (NU) members in the organization. This research uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation. Data is analyzed using the interactive analysis model from Miles and Huberman, which includes data reduction, data display, and conclusion drawing and verification. The validity of the data is strengthened through source triangulation.Research results show that the success of GP Ansor is determined by the selection of the right communicators, the formulation of relevant messages, and the use of social media such as Facebook as the main communication tool. Other media like WhatsApp also support internal communication within the organization. Despite facing obstacles such as technological limitations and competition between organizations, GP Ansor Ranting Kabat has managed to overcome these through regular study sessions, direct discussions, and active community involvement in various social activities. This research indicates that a communication strategy based on a combination of traditional and digital approaches is effective in enhancing citizen participation in organizational activities.